1996
DOI: 10.1111/j.1445-5994.1996.tb02933.x
|View full text |Cite
|
Sign up to set email alerts
|

Feed us nutrition: final year medical students' perceptions of nutrition medical education

Abstract: Newcastle medical students are interested in nutrition and believe it should be included in their medical curriculum. This may be due to their clinical exposure and the educational milieu of the University of Newcastle Medical School. Exposure to nutrition in their undergraduate education appears to be an important determinant for priority designated nutrition topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…In general, a high proportion of both medical practitioners and medical students were interested in nutrition and they wanted to know more about it. This is similar to the findings of other studies (Kushner, 1995;Warden et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In general, a high proportion of both medical practitioners and medical students were interested in nutrition and they wanted to know more about it. This is similar to the findings of other studies (Kushner, 1995;Warden et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Musaiger (1998) reported that adolescents are a neglected target group in health programmes in Arabian Gulf countries, as most of these programmes focus on the medical condition and health of mothers and children. These respondents were also more positive about giving nutritional advice to groups with clear medical problems than they were about giving it to other population groups, a result that is consistent with the findings of other investigators (Brett et al, 1986;Jack et al, 1990;Warden et al, 1996). This means that medical practitioners and medical students concentrate on nutrition for treatment of medical conditions more than health promotion for people in general.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation